Multiple myeloma: Report of a very rare case and review - Manoj Kumar Sachidanandan; Subha Manoharan; Karthik Rajaram; Mahesh Kumar; Palanisamy Parthiban Soundarapandi; Chandramouli Elumalai (Wolters Kluwer Medknow Publications, 2012)
Multiple myeloma consists of a clonal proliferation of plasma cells in the bone marrow, with varying degrees of differentiation. The disease is more frequently seen in men and the average age at diagnosis is about 60 years. The diagnosis is established by blood and urine examination and biopsy. Patients may present renal failure, bone pain, fatigue, recurrent infections and nervous system dysfunction. Oral manifestations may be the first sign of multiple myeloma, highlighting the importance of the dentist in the early diagnosis of the disease. This paper reports a case of multiple myeloma in a 72 years old male patient.